Bangkitnya Islam Radikal dan Nasionalisme: Studi tentang Gerakan Islam Wahabi - Arthur Aritonang (STT Iman Jakarta, 2020)
This article describes the contemporary phenomenon in which Muslims in Indonesia since the reform era have been indicated by the ideology of Wahhabism from the Middle East. From the beginning, one of the goals of NU's presence as the largest moderate Islamic organization in Indonesia and the world was to anticipate the inclusion of Wahhabism, which at that time was already widespread in the Middle East. During the new order radical Islamic character organizations did not have a place in this country but after the fall of the new order regime and then entered the era of reform (democracy and freedom of expression) radical-colored Muslims see this as a great opportunity whose basis is as governed by the Law namely the right to establish community organizations or political parties. This opportunity is used to build organizations in the name of Islam and then spread the doctrine of Wahhabism in Indonesia by building mosques, entering several pesantren, and even some Universitas in Indonesia have been exposed to radicalism. The activity was entirely sponsored by Saudi Arabia but not by the Saudi Arabian government. Therefore, the ideology of Wahhabism is clearly contrary to Pancasila and the spirit of nationalism because it actually endangers the existence of fellow Muslims, Christianity and other religions in Indonesia.AbstrakArtikel ini menguraikan fenomena kontemporer dimana umat Islam di Indonesia sejak era reformasi telah terindikasi oleh faham wahabisme dari Timur Tengah. Sejak semula, salah satu tujuan dari kehadiran NU sebagai organisasi Islam moderat terbesar di Indonesia maupun dunia, yaitu mengantisipasi masuknya faham wahabisme yang ketika itu sudah menyebar luas di Timur Tengah. Semasa orde baru organisasi Islam berwatak radikal tidak mendapat tempat di negeri ini, namun setelah tumbangnya rezim orde baru dan kemudian memasuki era reformasi (demokrasi dan kebebasan bereskpresi) umat Islam yang berwatak radikal melihat ini sebagai peluang besar yang dasarnya ialah sebagaimana yang diatur oleh Undang-Undang, yaitu hak untuk mendirikan organisasi kemasyarakat atau pun partai politik. Peluang ini dimanfaatkan untuk membangun organisasi yang mengatasnamakan Islam, kemudian menyebarkan doktrin wahabisme di Indonesia dengan cara membangun masjid, masuk ke beberapa pesantren, bahkan beberapa Universitas di Indonesia sudah terpapar radikalisme. Kegiatan tersebut seluruhnya disponsori oleh Arab Saudi, tetapi bukan berasal dari pemerintah Arab Saudi. Oleh karenanya, faham wahabisme jelas bertentangan dengan Pancasila dan semangat nasionalisme, sebab ini justru membahayakan bagi eksistensi sesama Islam, kekristenan dan agama-agama lainnya di Indonesia.